Analisis Pengaruh Penurunan Temperatur LMTD Terhadap Unjuk Kerja HRSG Pada PLTGU - Prayudi Suparmin (JURNAL POWERPLANT, 2019)
The Semarang Gas Generation and Steam Power Plant (PLTGU) is one type of combine cycle which is expected to support electricity needs. Heat Recovery Steam Generator (HRSG) is a device that has a working principle such as a boiler, without the need for additional fuel, an energy source from exhaust gases that have high temperature gas turbines. The problem that in HRSG is the occurrence of pipe leakage which results in the efficiency of HRSG. With overhaul, namely replacing the pipe, cleaning the tube wall, and isolating the HRSG, and plugging the tube, the overhaul has an impact on decreasing the logarithmic mean temperature difference (LMTD) and increase heat Q the impact of efficiency HRSG. This study was conducted to analyze the effect of decreasing LMTD temperature on HRSG performance before and after overhaul. The research method used is descriptive method by conducting a case study in the PLTGU Tambak Lorok Unit 2 Semarang. The data needed in the study was taken directly from the CCR of PLTGU Tambak Lorok Unit 2 Semarang. The results of the analysis showed that after overhaul activities resulted in a decrease in the difference in LMTD temperature and increased the amount of heat in the HRSG. The decrease in the difference in LMTD HRSG due to overhaul activity will result in increased HRSG efficiency, while the increase in heat Q HRSG after overhaul will increase the efficiency of HRSG